A study on factors that influence employee’s motivation in private sector / Nur Shahfinaz Salleh - Salleh, Nur Shahfinaz (Faculty of Business and Management, 2014)
The purpose of this research is to study the factors that influence employee’s motivation in private sector and the relationships between rewards, recognition, working environment and managerial trustworthiness. In addition, this study also will examine the level of employee’s motivation in private sector and several recommendations to increase employee’s motivation in private sector. In getting relevant data, 100 questionnaires were distributed to the employees that worked in any private sector around Tanjong Malim, Perak which is known as Education Town and has the potential of becoming a developed town at the Southern of Perak. Data collected were analyzed by using Statistical Package for Social Science (SPSS) program. This analysis includes the reliability test, frequency test, descriptive analysis test, Pearson correlation test and also regression test. Based on the findings, it shows that the most factor that influences employee’s motivation in an organization is Recognition followed by Working Environment. Thus, several recommendations such as employer should improve the working environment in an organization, the organization should improve their managerial trustworthiness and employer need to continuously improve the benefits given to all employees are included on this study in order to help employer to increase employee’s motivation in an organization in the way to achieve well performances.